Piroxicam-induced fixed drug eruption in palatal mucosa - Tomo, Saygo; da Silva Santos, Ingrid; da Silva Cunha, John L.; Miyahara, Glauco I. [UNESP]; Prado Ribeiro, Ana C.; dos Santos Silva, Alan R.; Simonato, Luciana E. (Wiley, 2021)
Background: Fixed drug eruption is a drug reaction characterized by the recurrent occurrence of erosive or ulcerative lesions in skin or mucosa surfaces upon the use of a specific drug. The occurrence of fixed drug eruption in oral mucosa is rare and ill documented. Case report: A 37-year-old woman who presented with recurrent erosive lesions in the palatal marginal gingiva of the upper first molars for 3 consecutive months. In anamnesis and follow-up, the time association with the intake of piroxicam to treat menstrual pain led us to the diagnosis of fixed drug eruption. Conclusion: Piroxicam is a rare culprit drug to fixed drug eruption, especially in oral mucosa.
Keywords: differential diagnosis; erosive; fixed drug eruption; gingival; mucosal; oral; palate